Adaptive morphology of the host-seeking first-instar larva of Stylops advarians Pierce (Strepsiptera, Stylopidae), a parasite of Andrena milwaukeensis Graenicher (Hymenoptera, Andrenidae). (September 2019) - Balzer, Zachary S.; Davis, Arthur R.
Abstract: The morphology of the prognathous, host-seeking first-instar larvae of Stylops advarians was examined to advance our understanding of their adaptations to reach immature bee hosts, a process requiring temporal phoresy on an adult bee. Sensory structures on the larval head, including eye spots and two pairs of olfactory pits, evidently assist recognition of an adult bee and eventual detection of a permanent host within a nest cell. First-instar larvae utilize various features of their appendages to travel securely on their phoretic host. Flexible adhesive tarsi of the pro- and mesothoracic legs allow them to embark and be retained on a flying bee. The tips of the pair of caudal filaments appear modified for a similar purpose. Spinulae of two lengths, and arranged in distinct patterns, cover the posterior edges of the thoracic and abdominal segments both dorsally and ventrally. These projections can cause lodging of larvae in the plumose hairs of the phoretic host, and may lock into the exine of pollen collected by the foraging bee. Discovery of a first-instar larva partially packed into a pollen load and in the crop of Andrena milwaukeensis demonstrates that Stylops is adapted to travel with a phoretic host both externally and internally. Highlights: Stylops first instars may be picked up by foraging phoretic hosts with the pollen. First instar Stylops larvae travel phoretically to find a permanent host. Miniaturized body of first instars is highly specialized for finding a permanent host. Stylops first instars likely can travel externally or internally with the phoretic host.